Mentoring and training for early childhood education teachers in facing the challenges of the Covid-19 pandemic situation - S. Sudiran; A. Adityo; Ria Arista Asih (Universitas Muhammadiyah Malang, 2023)
In Bandulan Village, Malang City, there are community of people dealing with the pandemic situation that need education for their children, but incapable to self-educate their children without the support of the teacher. This community service also aims to assist PAUD Mentari in providing free education to the children in local community. It is based on the phenomenon where teachers of this preschool face difficulties in carrying out common teaching practices concerning the pandemic of Covid-19. A community service team implement a series of professional development activities to enhance teachers’ skills in schooling management and crafting teaching media. The community service employs ADDIE approach. Outcomes of this professional development activities are in the forms of the PAUD Mentari teachers’ simple schooling management plan and crafted teaching media. These outcomes scaffold the implementation of effective early education schooling in a local community during this pandemic. The results of the Community Service showed that Early Childhood Mentari School teachers' readiness for distance learning during the Covid-19 Pandemic can be said to be good with educational standards facilities. During the pandemic, the PAUD Mentari school implemented a conducive learning model equipped with an online learning of Google Classroom application. Moreover, there are several aspects of the teaching and learning process at PAUD Mentari during the Covid-19 pandemic such as, distance learning, sharing learning materials digitally, support and communication with parents, creative learning activities, monitoring and evaluation, counseling and emotional support.